Hubungan Antara Tingkat Depresi Dengan Kualitas Hidup Lanjut Usia Di Panti Wredha Darma Bhakti Pajang Surakarta - Diena Azzahro, Fahma, Fahrun Nur Rosyid, S. Kep., Ns., M. Kes (2016)
Depression is a psycological problem that is marked by the deep feelings of sadness and influence physical activity. Quality of life is a person's perception of how much an individual can carry out its function in daliy life. Quality of life divided into 4 domain are pysical, psycological, social contact and area contact. The purposes of this research is to know correlation between levelof depression with quality of elderly life at Panti Wredha Darma Bhakti Pajang Surakarta. This research is non eksperimental quantitative research with the kind of correlation. The research design used is cross secctional. The research sample are consist 58 of elderly were taken using total sampling technique. It is done by distributing questionnaire GDS (Geriatric Depression Scale) and modification of WHOQOL (World Health Organization Quality of Life). The result of this research is analyzed with descriptive analitic method. Bivariate analysis using Rank Spearman obtained result -0,435 (p-value = 0,001). So it concluded there is a correlation between level of depression with quality of elderly life at Panti Wredha Darma Bhakti Pajang Surakarta.